Estudio de Factibilidad para la Implementación de una Empresa de Transporte Terrestre de Carga para Servir a las PYMES en la Ciudad de Loja - Cevallos Bravo, Lauro Miguel (2016)
In the city and province of Loja, the mode of transport used is the Land transport as it has the Panamerican Highway and roads of second and third order that unite all cantons with only a few hours travel to supply the different types of goods necessary to satisfy end customers. As this project is a feasibility study, the focus is on the knowledge of the current business situation of freight transport, in which some embedded companies operate in this activity and have their actions and experience gained in a few years .. The heavy road transport shows a growth rate in recent years exceeding 10%, becoming such an important sector not only for its service but as an integrated entity of peoples and regions. Recognizing this approach, the project is presented as part of a solution to a growing demand for efficient services. It is so decided to perform a feasibility study for implementation of a transport company in the Heavy Duty Loja City serving mainly of SMEs in the provinces of Loja, Zamora Chinchipe and El Oro, particularly the Uptown cantons are like Zaruma, Portovelo, Atahualpa and pineapples, and other sites such as Quito, Guayaquil and Cuenca are supply centers and exchange with the city of Loja .. Market research, determine the unmet demand of heavy cargo, market segment, and the most appropriate marketing channels, as well as the acceptance of the service aspects that need improvement and the prices that consumers pay in the different routes, all this by conducting a survey of a sample of SMEs load generators in the city of Loja. Through technical study, project size, location, constitution and legal structure of the company is determined. 5 The financial analysis indicates the investment of $ 619 180.00 with a contribution of 64% of equity and 36% equity funded by the National Finance Corporation within three years. The project assessment methods are mainly based on appropriate information, extracted from the economic analysis, especially in the financial statements. Measuring the level of usefulness of this project is obtained that the net present value is $ $ 217.800.y a rate of return of 25.13% with a value of 1.63 and benefit discount rate of 22.73%, which ensure the financial viability of the project.